Implementation of the Decision Tree Algorithm as an English Learning Media at SD Negeri 1 Senenan - R Hadapiningradja Kusumodestoni; Gun Sudiryanto; Gentur Wahyu Nyipto Wibowo; Charles Firmansyah (Formosa Journal of Applied Sciences, 2022)
This research is motivated by the declining interest of students in learning English because teaching the old or traditional way more or less hinders the ability of many students to understand certain languages. The purpose of this research is to design an English learning media in the form of educational games to attract students' interest in learning English further. This research uses the waterfall development method which is combined using the Decision Tree algorithm. In its application the Waterfall method has five stages, namely, Requirements Analysis, System Design, Program Code Writing, Testing, and Maintenance, while the application of the Decision Tree algorithm lies in the first game to choose what path or scan will each player get. The results of this study showed that 90.85% of people who took part in the survey through respondent questionnaires were interested in learning more English.